Relapses in Alcohol and Cocaine Dependence in Spousal Relationships: A Behavioral Assessment with Couple - Silva, Adriana Madeira Alvares; Borloti, Elizeu; Ferrari, Jaqueline Vago (Advances in Social Sciences Research Journal, 2024)
Contingency analysis is a central concept and method in behavior analysis for understanding how the environment influences human behavior. In the treatment of chemical dependency, this analysis makes it possible to examine the functional relationships between antecedent stimuli, behaviors, and consequences (antecedent-behavior-consequence model) in order to understand and modify behavior. Through contingency analysis, professionals can personalize and adapt interventions according to the individual needs of substance-dependence patients, making it a fundamental tool in the multidisciplinary approach to relapse prevention. The purpose of this article is to conduct analyses of contingencies described in reports of relapse episodes of psychoactive substance use by individuals diagnosed with alcohol dependence and cocaine dependence, formally married, throughout their spousal behavioral histories. Based on detailed and systematic information about more than one case in comparison, contingency analyses of relapse episodes were conducted. The study sample consisted of four heterosexual couples (total N = 8), with one individual in the couple diagnosed with alcohol or cocaine dependence. The selection was made through the Rehabilitation Program of a Military Police Hospital located in Vitória/ES, Brazil. The analyses revealed common contingencies, including social pressure (from the friends’ group with their invitations), negative emotional states (elicited by plans gone wrong, adverse conditions), and physiological dependence (craving, withdrawal syndrome, tolerance, and salience of use). The specificity of the spousal relationship provided the nuance for these contingencies, emphasizing the importance of therapeutic interventions with couples to assist in preventing relapses, including stress management skills, craving coping, conflict resolution, frustration tolerance, and communication.